Compression Therapy for Prevention of Chemotherapy-Induced Peripheral Neuropathy: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Wan Z; Huang J; Wang X; Li P (Journal of Pain Research)
Zhanhai Wan,1 Jiajie Huang,2 Xiumei Wang,1 Peng Li1 1Department of Anesthesiology and Operating Theater, The First Hospital of LanZhou University, Lanzhou, Gansu, People’s Republic of China; 2School of Nursing, Gansu University of Chinese Medicine, Lanzhou, Gansu, People’s Republic of ChinaCorrespondence: Peng Li, Email Leepeng19771125@163.comBackground: Chemotherapy-induced peripheral neuropathy (CIPN) significantly impairs the quality of life of patients undergoing chemotherapy and diminishes their adherence to the treatment regimen. Existing studies suggest that compression therapy may prevent the onset of CIPN, yet the specific efficacy remains to be conclusively determined.Methods: We performed a systematic review and meta-analysis of randomized controlled trials (RCTs) comparing compression therapy with inactive comparators in patients scheduled for chemotherapy. Evidence certainty was evaluated using the GRADE approach.Results: Analysis of four trials (442 patients) revealed that compression therapy reduced CIPN incidence (RR = 0.50, 95% CI: 0.33– 0.76; absolute effect = − 265, 95% CI: − 355 to − 127 per 1000) and depression (SMD = − 0.83, 95% CI: − 1.21 to − 0.45) with moderate evidence and high adherence. No significant differences emerged in anxiety, sleep quality, or pain.Conclusion: Moderate- to low-certainty evidence supports compression therapy’s effectiveness in preventing CIPN and alleviating depression while showing no substantial impact on other outcomes.Limitation: Evidence quality and quantity suggest potential bias, warranting additional RCTs to strengthen the evidence base.Keywords: compression therapy, CIPN, RCT